Delivering specialised care to people ageing with HIV in the UK: experience and evolution of services from 2009 to 2019. (March 2022) - Milinkovic, Ana; Pereira, Branca; Mazziteli, Maria; Girometti, Nicolo; Asboe, David; Pozniak, Anton; Boffito, Marta
Summary: Background: The introduction of antiretrovirals has resulted in a demographic shift with an increasing proportion of people living with HIV older than 50 years and a change in the spectrum of diseases affecting this population. A specialised clinical service dedicated to older people living with HIV was implemented at Chelsea and Westminster Hospital, London, UK in 2009, following training of health-care providers in HIV, ageing, comorbidity, and polypharmacy management. We report the results of a service evaluation reviewing 10 years of activity of this specialised clinic, including lessons to be applied in routine practice. Methods: We estimated the prevalence of multimorbidity and polypharmacy and described algorithms devised for use across our HIV outpatient services following implementation of the specialised clinical pathway. The service evaluation was approved by our local clinical governance system and data relative to the period 2009–19 were collected on a secured trust database. Findings: Dedicated time was created for senior and junior doctors, a nurse, and a pharmacy to create clinical appointments for older people living with HIV referred by all service care providers. The team would review different clinical scenarios, book follow-up appointments to review results, refer to different specialists or to complex multidisciplinary teams when necessary. 744 people with HIV aged 50 years and older attended our services (93% [691] male, 7·1% [53] female; mean age 56·5 years [SD 5·5]; 84·2% [622] White, 7·5% [56] Black, 0·9% [7] Asian, 7·5% [56] other race or ethnicity). The prevalence of multimorbidity was 69·3% and of polypharmacy was 46·6%. The most common comorbidities were vitamin D deficiency (428 of 690, 62%), dyslipidaemia (373, 50·1%), hypertension (157, 21·5%), depressive or anxious disorders (117, 15·8%), osteoporosis (91, 12·2%), obesity (98, 13·2%), chronic kidney disease (56, 7·5%), and diabetes (43, 5·7%). Patients with dyslipidaemia, osteoporosis, and metabolic disorders were referred to a live well pathway clinic focusing on targeted lifestyle interventions, including diet and physical exercise, under the supervision of a dietician and a physiotherapist. Interpretation: We have described how our HIV over-50 clinic was organised and implemented, and we reported data showing high rates of comorbidities and polypharmacy, which led to the establishment of a specialised care pathway for all HIV care providers and to the implementation of further joint HIV and specialty clinics (cardiology, metabolic, menopause, nephrology, neurology, and geriatric). Funding: None.